THE VALANGINIAN WEISSERT OCEANIC ANOXIC EVENT RECORDED IN CENTRAL-EASTERN SARDINIA (ITALY) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2018)
Investigations on the S’Ozzastru section from the northern part of the Mt Albo area (central-eastern Sardinia, Italy) for integrated litho- bio- and chemostratigraphy allowed the identification of the Valanginian Weissert Oceanic Anoxic Event (OAE), testified by a positive carbon isotope excursion (CIE). The section, which represents the deepest-water succession of the Valanginian in Sardinia, is composed of the Schiriddè Limestone followed by the Siniscola Marl, both proposed as new lithostratigraphic units. The presence among the ammonites of Busnardoites campylotoxus allows the attribution of the Schiriddè Limestone to the upper Lower Valanginian Campylotoxus Zone auctt. (= Karakaschiceras inostranzewi Zone of Reboulet et al. 2014). Further characterization of this unit was not possible since it is barren/almost barren of nannofossils. The Siniscola Marl can be ascribed to the lower Upper Valanginian on the basis of the ammonite fauna indicating the Verrucosum Zone, and of the nannofossil content suggesting the Zone NK3. The carbon isotope record in the Siniscola Marl is characterized by a positive excursion with values up to 2.98 ‰. In the nannofossil assemblages, nannoconids are not particularly abundant and are found, among others, together with C. oblongata, D. lehmanii, and pentaliths. The scarcity of nannoconids is regarded as a biostratigraphic support for the identification of the Weissert OAE, as it possibly reflects the “nannoconid decline” interval which characterizes this event. The end of the Weissert OAE CIE is not recorded probably because of tectonic causes.